Allergic dermatitis in a bull: a case report - Abdullah, Faez Firdaus Jesse; Tijjani, Abdul Nasir; Abba, Yusuf; Adamu, Lawan; Mohammed, Konto; Osman, Abdinasir Yusuf; N., Syariha; Ahmad Affandi, Syahirah; Haron, Abdul Wahid (Global Researchers Journals, 2014)
A case of skin lesions in a 2 year old Kedah-kelantan cross bull was presented to the Large Animal unit of the University Veterinary Hospital, Universiti Putra Malaysia. Physical examination revealed that the vital parameters were all within the normal range. However, there were multiple circumscribed skin lesions (1-2cm) along the dorsal spine and on all the limbs. Examination of the farm house environment revealed marshy areas with Cullicoides infestations. The wound was dressed with diluted chlorhexidine and povidone iodine followed by topical application of dermapred (antibacterial + anti-inflammatory) agent. The bull was given intramuscular injections of chlorpheniramine melate 1ml/50kg, Penicillin 15mg/kg and flunixin meglumine1.1mg/kg. The haemogram showed lymphocytosis, monocytosis, eosinophilia, basophilia and neutrophilia with left shift. The farmer was advised to clear the bush and drainages around the farm. A follow up visit to the farm one week after the treatment showed a significant improvement as the wound had dried up and the lesions are healing.